ANALYSIS OF SNACK G SALES FORECAST AT CV. GATSU JAYA PERKASA ABADI USING NAIVE FORECAST, EXPONENTIAL SMOOTHING AND LINEAR REGRESSION METHOD - Sylvia Sylvia (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Forecast is important tool and method for effective and efficient company operation. In the midst of food and beverage fierce competition, the accurate forecast for product sales has important role for company’s competitive edge. This research is conducted at CV Gatsu Jaya Perkasa Abadi (food and beverage industry), located in North Sumatra. Currently the sales forecast by CV Gatsu Jaya Perkasa Abadi are using the previous period sales data and intuitive to forecast sales for the next period, thus, the forecast is not accurate and results in inefficient and ineffective. In this research, the forecast methods that will be analyzed are exponential smoothing and linear regression method and comparing the forecast deviation versus actual data among exponential exponential smoothing, linear regression and naïve forecast (which currently used by company). The purpose of the research is to recommend the accurate forecast method to company which the recommendation will be based on minimum error (deviation) using MAD dan MAPE between actual data and forecast of snack G product. Research methods that are used in this paper are interview, observation, historical data collection and literature study to support the discussion and analysis of the research. The research analysis result shows the best forecast method for snack G sales at CV Gatsu Jaya Perkasa Abadi is using linear regression method with smallest MAD and MAPE.